Hitler and the Nazis : a history in documents - Crew, David F. 1946- (Pages from history, 2005)
Presents a history of the rise and fall of Hitler and Nazism through original source documents, including Nazi party records and propaganda and documents from witnesses, Holocaust survivors, and individuals who resisted the Nazi regime.